Mechanical Engineering - Murat Gokcek (IntechOpen, 2012)
The book substantially offers the latest progresses about the important topics of the'Mechanical Engineering'to readers. It includes twenty-eight excellent studies prepared using state-of-art methodologies by professional researchers from different countries. The sections in the book comprise of the following titles: power transmission system, manufacturing processes and system analysis, thermo-fluid systems, simulations and computer applications, and new approaches in mechanical engineering education and organization systems.